2015
DOI: 10.1080/1540496x.2015.1103137
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Macroprudential Policies in Developing Asia: An Empirical Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This finding completes the unfinished puzzle from previous estimation. This result is in accordance with the empirical studies of Wimanda et al (2014), Lee et al (2015) and Lim et al (2011). Therefore, the argument that LTV instrument which capable in affecting intermediate objective (credit risk) but not effectively affecting overall risk can be explained by this model.…”
Section: Modified Empirical Models' Estimation Result: Credit Risk (Rsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding completes the unfinished puzzle from previous estimation. This result is in accordance with the empirical studies of Wimanda et al (2014), Lee et al (2015) and Lim et al (2011). Therefore, the argument that LTV instrument which capable in affecting intermediate objective (credit risk) but not effectively affecting overall risk can be explained by this model.…”
Section: Modified Empirical Models' Estimation Result: Credit Risk (Rsupporting
confidence: 93%
“…The last category consists of empirical studies which show that macroprudential policy is effective in influencing intermediate objectives. Lee et al (2015) found that credit-related policies significantly decrease credit expansion and housing price rise, whereas liquidity-related policies effectively reduce leverage and rapid increase in housing price. Claessens et al (2014) and Lim et al (2011) found consistent results in assessing the impact of macroprudential policy instruments on financial stability.…”
Section: Macroprudential Policiesmentioning
confidence: 99%
“…A number of studies attempted to address this problem. Tillmann [ 52 ] and Lee et al [ 44 ] employed a Qual VAR (VAR augmented by qualitative variables) to convert binary data on macroprudential shocks into more continuous ones. Zhang and Tressel [ 55 ] mapped various macroprudential policy instruments to factors that affect changes in bank lending standards (for example, they did not use dummies for LTV requirements, but looked at changes in LTV lending standards from bank surveys).…”
Section: Measuring the Impact Of Macroprudential Policy: Literature Reviewmentioning
confidence: 99%
“…The policy is taken by Bank Indonesia, other than adjusting the Benchmark Interest Rate, which is to run the macroprudential policy. Macroprudential policy is a measure taken to maintain the stability of the financial system, comprehensively oriented, and to minimize systematic risk (Bank Indonesia, 2016;Lee, Asuncion, & Kim, 2016). Systematic risk is a risk that causes the loss of public trust and the increase of uncertainty within the financial system, disrupting the progress of the financial system and economic process (Bank Indonesia, 2016: 4).…”
Section: B Maintaining Rupiah Stability Through Macroprudential Policymentioning
confidence: 99%